Management Of Trichobezoar With And Without Rapunzel Syndrome In Tertiary Care Centre - Talwar, Ashutosh; Singh, Amandeep; Kaur, Manpreet; Kaur, Haramritpal (Journal of Society of Surgeons of Nepal, 2025)
Trichobezoar is a rare pathology in which swallowed hairs accumulate in the stomach. An unusual form of bezoar extending from the stomach to the small intestine or beyond has been described as Rapunzel syndrome. Trichobezoars typically cause abdominal pain and nausea, but can also present as an asymptomatic abdominal mass, progressing to abdominal obstruction and perforation. Trichobezoar with Rapunzel syndrome is an uncommon diagnosis. It is predominantly found in emotionally disturbed or mentally retarded young people. The diagnosis may be suspected in young females with abdominal pain, epigastric mass and malnutrition, who have a history of trichophagia. The Authors present a series of three cases treated successfully by laparotomy and removal of trichobezoars. Psychodynamic aspects, clinical manifestations, diagnosis and therapeutic strategies are discussed.